2017
DOI: 10.1038/srep45060
|View full text |Cite
|
Sign up to set email alerts
|

Therapy targeted to the metastatic niche is effective in a model of stage IV breast cancer

Abstract: Treatment of stage IV metastatic breast cancer patients is limited to palliative options and represents an unmet clinical need. Here, we demonstrate that pharmacological inhibition of miRNA-10b - a master regulator of metastatic cell viability – leads to elimination of distant metastases in a mouse model of metastatic breast cancer. This was achieved using the miRNA-10b inhibitory nanodrug, MN-anti-miR10b, which consists of magnetic nanoparticles, conjugated to LNA-based miR-10b antagomirs. Intravenous injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 14 publications
3
53
0
Order By: Relevance
“…Synthesis of the prototype nanodrugs have been previously described by us 6,29 and involved: (1) synthesis of dextran-coated magnetic nanoparticles 30 ; (2) conjugation of Cy5.5 fluorescent dye. The number of dyes per magnetic nanoparticle was determined as 3.2 (6); (3) conjugation of antisense LNA inhibiting oligonucleotides (ASO) or miRNA mimics through heterobifunctional linker N-succinimidyl 3-[2-pyridyldithio]-propionate (SPDP; Thermo Scientific Co., Rockford, IL) to produce MN-ASO or MN-miRNA [31][32][33] . ASO-scrambled (MN-ASOscr, single stranded) and mimics-scrambled (MN-miRNAscr, double stranded) nanodrugs were also synthesized as controls.…”
Section: Synthesis and Characterization Of Mir-216a Nanodrugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of the prototype nanodrugs have been previously described by us 6,29 and involved: (1) synthesis of dextran-coated magnetic nanoparticles 30 ; (2) conjugation of Cy5.5 fluorescent dye. The number of dyes per magnetic nanoparticle was determined as 3.2 (6); (3) conjugation of antisense LNA inhibiting oligonucleotides (ASO) or miRNA mimics through heterobifunctional linker N-succinimidyl 3-[2-pyridyldithio]-propionate (SPDP; Thermo Scientific Co., Rockford, IL) to produce MN-ASO or MN-miRNA [31][32][33] . ASO-scrambled (MN-ASOscr, single stranded) and mimics-scrambled (MN-miRNAscr, double stranded) nanodrugs were also synthesized as controls.…”
Section: Synthesis and Characterization Of Mir-216a Nanodrugsmentioning
confidence: 99%
“…ASO-scrambled (MN-ASOscr, single stranded) and mimics-scrambled (MN-miRNAscr, double stranded) nanodrugs were also synthesized as controls. The number of oligos per MN was determined as 4.0 using the electrophoresis analysis method described previously 33 .…”
Section: Synthesis and Characterization Of Mir-216a Nanodrugsmentioning
confidence: 99%
“…In our own studies, we identified miRNA-10b as a master regulator of the viability of metastatic tumor cells. We determined that miR-10b not only promotes the capacity of tumor cells to migrate and invade surrounding tissue (become metastatic) but also serves as a powerful master regulator of the viability of these cells ( 133 135 ). Detailed mechanistic studies confirmed the existence of a miR-10b-triggered pathway that regulates the viability and proliferation of tumor cells only after they have acquired the ability metastasize, pointing to miR-10b as a driver of resistance to anoikis ( 134 ).…”
Section: Examples Of Therapeutic Interventions That Fit the Paradigm mentioning
confidence: 99%
“…In a model of Stage IV metastatic breast cancer, we found that a weekly treatment protocol with MN-anti-miR-10b and low-dose doxorubicin demonstrated complete regression of pre-existing lung metastases in 65% of the animals and inhibition of multiple organ metastases in 94% of the animals. This translated into a significant reduction in cancer mortality in animals treated with MN-anti-miR10b and low-dose doxorubicin relative to control groups, including a group treated with monotherapy of standard dose doxorubicin, used to model standard-of-care ( 135 ).…”
Section: Examples Of Therapeutic Interventions That Fit the Paradigm mentioning
confidence: 99%
“…In our own work, we have strived to incorporate imaging of drug delivery as an indispensable companion to drug development. We have extensively used dextran coated iron oxide nanoparticles as delivery vehicles for siRNA or antagomir therapeutics to tumors ( 26 31 ).…”
Section: Imagingmentioning
confidence: 99%